Microbial Biosurfactants as Key Multifunctional Ingredients for Sustainable Cosmetics - Hamid-Reza Ahmadi-Ashtiani; Anna Baldisserotto; Elena Cesa; Stefano Manfredini; Hossein Sedghi Zadeh; Mostafa Ghafori Gorab; Maryam Khanahmadi; Samin Zakizadeh; Piergiacomo Buso; Silvia Vertuani (Cosmetics, 2020)
A polar head and an apolar tail chemically characterize surfactants, they show different properties and are categorized by different factors such as head charge and molecular weight. They work by reducing the surface tension between oil and water phases to facilitate the formation of one homogeneous mixture. In this respect, they represent unavoidable ingredients, their main application is in the production of detergents, one of if not the most important categories of cosmetics. Their role is very important, it should be remembered that it was precisely soaps and hygiene that defeated the main infectious diseases at the beginning of the last century. Due to their positive environmental impact, the potential uses of microbial sourced surfactants are actively investigated. These compounds are produced with different mechanisms by microorganisms in the aims to defend themselves from external threats, to improve the mobility in the environment, etc. In the cosmetic field, biosurfactants, restricted in the present work to those described above, can carry high advantages, in comparison to traditional surfactants, especially in the field of sustainable and safer approaches. Besiede this, costs still remain an obsatcle to their diffusion; in this regard, exploration of possible multifunctional actions could help to contain application costs. To highlight their features and possible multifunctional role, on the light of specific biological profiles yet underestimated, we have approached the present review work.